What teens need to succeed : proven, practical ways to shape your own future - Benson, Peter L. (Free Spirit Publishing, 1998)
Describes forty "developmental assets" that teenagers need to succeed in life, such as family support, positive peer influences, and religious community, and suggests ways to acquire these assets.